Research of Social Inequality of the Population in the Regions of Kazakhstan (Global Journal of Human-Social Science, 2023)
Under the conditions of the negative impact of global economic geopolitical climatic and epidemiological risks the income gap between different social strata of the population in different regions of the Kazakhstan is growing Therefore the reduction of social inequality of the population is an important problem The purpose of the article is to study theoretical and practical issues of social inequality and develop recommendations for its reduction in Kazakhstan The hypothesis of the study is the assumption about the growing inequality of the population living in different regions of Kazakhstan The article summarizes the theoretical views of scientists on the problems of inequality examines the dynamics of key indicators reflecting the standard of living of the population in the regions of Kazakhstan The conclusion is made about the strengthening of social inequality of the population living in different regions of the country Measures have been developed to reduce it
Keywords: social inequality; income of the population; inclusive development; region; socio-economic development; poverty